2015
DOI: 10.15547/bjvm.869
|View full text |Cite
|
Sign up to set email alerts
|

Welfare improvement in laying hens during the hot period under a semi-open rearing system through dietary arginine and vitamin C supplementation

Abstract: The welfare assessment model in poultry under different rearing systems has gained increasing importance. An economically profitable approach for improvement of laying hens welfare during the hot summer period is diet's supplementation with specific additives (microelements, vitamins, and minerals) to satisfy the body's needs under heat stress. The purpose of the present study was to evaluate the welfare of DeKalb Brown laying hens (n=295) whose feed was supplemented with either 10 mg/kg Larginine or with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
2
3
0
1
Order By: Relevance
“…In summer, with temperatures temporarily reaching up to 30°C, turkeys appeared to be less active. It could be suggested that the observed decrease in activity associated with high temperatures resulted in lower frequencies of feather pecking, as previously described by BOZAKOVA et al (2009), and less injurious pecking were responsible for the lower separation rates. Regarding different stocking densities, a distinct picture arose when comparing the two trials.…”
Section: Discussionsupporting
confidence: 69%
“…In summer, with temperatures temporarily reaching up to 30°C, turkeys appeared to be less active. It could be suggested that the observed decrease in activity associated with high temperatures resulted in lower frequencies of feather pecking, as previously described by BOZAKOVA et al (2009), and less injurious pecking were responsible for the lower separation rates. Regarding different stocking densities, a distinct picture arose when comparing the two trials.…”
Section: Discussionsupporting
confidence: 69%
“…However, similar to this study Kucuk et al (2003a) reported that in the laying hens under stress 250 mg/kg of vitamin C diet decreased serum triglyceride compared with control group. As well as, Bozakova et al (2015) reported in the laying hens under heat stress total cholesterol, glucose and triglycerides decreased but increased the total protein with 10 mg per kg of arginine + 250 mg per kg of vitamin C diet. These results might have been due to decreased corticosterone (catabolic) and increased insulin (anabolic) concentrations upon vitamin supplementations.…”
Section: Discussionsupporting
confidence: 60%
“…Over-supplementation was detrimental from 1 to 3 weeks of age ( Chamruspollert et al, 2004 ), neutral from 3 to 6 weeks of age ( Mendes et al, 1997 ), and beneficial from 6 to 8 weeks of age ( Brake, 1998 ). Arg supplementation also improved FCR of Pekin ducks exposed to cyclic HS ( Zhu et al, 2014 ) and enhanced several welfare indicators and decreased corticosterone plasma concentration in laying hens during the hot summer period ( Bozakova et al, 2015 ). Furthermore, increasing dietary Arg improved performance, reproduction, antioxidant status, immunity, and maternal antibody transmission in quails ( Kalvandi et al, 2022 ).…”
Section: Supplementation Of Amino Acidsmentioning
confidence: 99%